Legal Protection for Borrowers in Default on Online Loan Agreements - Kristianto Jansen Hengkengbala; Weny Almoravid Dungga; Zamroni Abdussamad (Yayasan Cerdas Pedia Indonesia, 2026)
This study critically examines the complex intersection of debtor default, personal data protection, and algorithmic governance within P2P lending platforms operating in Indonesia. Classical contract law under the Civil Code consistently fails to accommodate the structural asymmetries of digital agreements, wherein personal data is illegally weaponized as a de facto guarantee during default debt collection. Employing a normative legal methodology with both statutory and conceptual approaches, this paper systematically deconstructs the persistent illusion of preventive and repressive consumer protection mechanisms. The findings reveal that digital consent is systematically manufactured through predatory dark patterns, while existing dispute resolution frameworks remain slow against real time, irreversible social character assassination. Consequently, this study introduces the novel paradigm of integrated strict liability. This prescriptive model dictates that any algorithmic privacy violation by fintech platforms automatically forfeits their civil debt recovery rights, rendering the underlying electronic loan agreement null and void to definitively restore equity.